2017
DOI: 10.1902/jop.2016.160217
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Bifidobacterium animalis subsp. lactis Probiotic in Experimental Periodontitis

Abstract: Topical use of B. lactis HN019 promotes a protective effect against alveolar bone loss and CTALs attributable to EP in rats, modifying immunoinflammatory and microbiologic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
128
1
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 85 publications
(168 citation statements)
references
References 47 publications
(91 reference statements)
8
128
1
14
Order By: Relevance
“…In a preclinical study, Oliveira et al. () demonstrated that B. lactis HN019 reduces the amount of periodontopathogens on biofilm. The possible coaggregation of Bifidobacterium with Fusobacterium nucleatum can reduce the amount of binding sites for periodontopathogens on biofilm (Haukioja et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a preclinical study, Oliveira et al. () demonstrated that B. lactis HN019 reduces the amount of periodontopathogens on biofilm. The possible coaggregation of Bifidobacterium with Fusobacterium nucleatum can reduce the amount of binding sites for periodontopathogens on biofilm (Haukioja et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Only two pre‐clinical studies evaluated the effect of bacteria of the genus Bifidobacterium on periodontal disease (Oliveira et al., ; Ricoldi et al., ). Oliveira et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…lactis , named HN019, on the development of experimental periodontitis (EP) in rats. It was observed that the treatment promoted a protective effect against periodontal breakdown, modifying immunoinflammatory and microbiological parameters [17]. To the best of our knowledge, there are no studies evaluating the effects of B .…”
Section: Introductionmentioning
confidence: 99%